Characteristic and viability of nitrogen fixation bacteria and phosphate solubilizing bacteria in carrier media - Umadi, Sarah Sakinah; Ilyas, Satriyas; Widyastuti, Rahayu (Jurnal Ilmu Tanah dan Lingkungan, 2023)
A consortium of nitrogen-fixing bacteria and phosphate solubilizers serves as biological fertilizers to increase the availability of plant nutrients such as nitrogen (N) and phosphorus (P). The experiment aims to study the character of nitrogen-fixing bacteria and phosphate solubilizing bacteria and compare their viability on the biochar (made from husk charcoal and corn cobs) as the carrier media. The experiment involved several tests, such as pathogenicity, nitrogen-fixing ability, phosphate solubilization ability on solid Pikovskaya media, compatibility, and viability. The results showed that KPB4 isolates were pathogenic to animals or humans. Nitrogen-fixing bacteria isolates, namely KBP1, KBP2, and KBP5, had N solubility (ppm) of 54.86, 77.79, and 76.28, respectively, and had NH3 concentrations (mg/L) of 66.61, 94.46, and 92.63, respectively. BPF9 (phosphate solubilizing bacteria isolate) had a phosphate solubilization index of 1.14. Each isolate of nitrogen-fixing bacteria was compatible with BPF9. The results showed that KBP2 and KBP5 each consorted with BPF9 on corncob biochar carriers had higher bacteria populations (15.50 x 107 CFU/g) after four weeks of storage.Keywords: nitrogen-fixing, phosphate solvent, consortium bacteria, biochar